The status of implementation of the CGIAR Principles on the Management of Intellectual Assets: A submission from CGIAR to the Tenth Session of the Plant Treaty’s Governing Body - CGIAR (2023)
This is the third report from CGIAR to the Governing Body of the International Treaty on Plant Genetic Resources for Food and Agriculture (Plant Treaty) concerning the status of the implementation of the CGIAR Principles on the Management of Intellectual Assets (CGIAR IA Principles).